2018
DOI: 10.1186/s12904-018-0315-3
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care for patients with cancer: do patients receive the care they consider important? A survey study

Abstract: BackgroundIn many countries, GPs and home care nurses are involved in care for patients with advanced cancer. Given the varied and complex needs of these patients, providing satisfactory care is a major challenge for them. We therefore aimed to study which aspects of care patients, GPs and home care nurses consider important and whether patients receive these aspects.MethodsSeventy-two Dutch patients with advanced cancer, 87 GPs and 26 home care nurses rated the importance of support when experiencing symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 27 publications
(22 reference statements)
2
17
0
4
Order By: Relevance
“…The main reasons for asking for IPCC support seems to be physical symptom burden and help in organizing further care. The former is consistent with results of earlier studies throughout different countries [38][39][40], and is a very common connotation of PC. Organization of further care in terms of support in organizing home or hospice care or transferring patients to PC units was a frequently addressed issue and seems to be more present than in other studies.…”
Section: Discussionsupporting
confidence: 92%
“…The main reasons for asking for IPCC support seems to be physical symptom burden and help in organizing further care. The former is consistent with results of earlier studies throughout different countries [38][39][40], and is a very common connotation of PC. Organization of further care in terms of support in organizing home or hospice care or transferring patients to PC units was a frequently addressed issue and seems to be more present than in other studies.…”
Section: Discussionsupporting
confidence: 92%
“…It can therefore be challenging for patients to remain at home for as long as they would like. It has been found that older patients with cancer who live alone make plans for death, but not for dying [56]. This underlines the need for healthcare professionals to focus on advanced care planning, especially for patients living alone, taking account of the fact that care aid support and health technology can have the potential to provide them with a sense of security [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Exploring what care users find important aspects of good-quality palliative care and relating this to their actual experiences may provide a more valid picture and may also provide insight into the care aspects where quality improvements are most needed. For this reason, Heins et al (2018) performed a survey study using parts of the Palliative Care Consumer Quality Index [9] in which advanced cancer patients’ actual care experiences were compared to the ratings they gave for the importance of 13 items regarding information provision, respect for their autonomy and support when suffering from pain or other symptoms [10]. Seventy-two home-dwelling Dutch patients with advanced cancer participated, and almost all rated all 13 items as important.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the palliative care that patients received matched with what they considered as important. However, improvements could be made in the provision of support to patients suffering from fatigue and in the provision of information on the expected course of patients’ illness [10]. A limitation of this quantitative survey was, however, that respondents had limited opportunities to give in depth-information about their perspectives or to mention new topics that are also important to them.…”
Section: Introductionmentioning
confidence: 99%